2021
DOI: 10.3389/fonc.2021.737368
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Study of Radiomics and Deep-Learning Based Methods for Pulmonary Nodule Malignancy Prediction in Low Dose CT Images

Abstract: ObjectivesBoth radiomics and deep learning methods have shown great promise in predicting lesion malignancy in various image-based oncology studies. However, it is still unclear which method to choose for a specific clinical problem given the access to the same amount of training data. In this study, we try to compare the performance of a series of carefully selected conventional radiomics methods, end-to-end deep learning models, and deep-feature based radiomics pipelines for pulmonary nodule malignancy predi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 43 publications
1
15
0
Order By: Relevance
“…Radiomics with ML and DL are active research in the field of oncology ( 17 ). Some studies showed that the DL model had better performance than the ML-based radiomics ( 18 20 ), some showed ML-based radiomics out-performed DL model ( 21 ), and some demonstrated DL-based radiomics model had the best performance ( 22 , 23 ). Prior studies had performed radiomics based ML or DL to classify thymoma form other PMT ( 24 26 ).…”
Section: Discussionmentioning
confidence: 99%
“…Radiomics with ML and DL are active research in the field of oncology ( 17 ). Some studies showed that the DL model had better performance than the ML-based radiomics ( 18 20 ), some showed ML-based radiomics out-performed DL model ( 21 ), and some demonstrated DL-based radiomics model had the best performance ( 22 , 23 ). Prior studies had performed radiomics based ML or DL to classify thymoma form other PMT ( 24 26 ).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the combination of hand-crafted features and deep features improves the classification or regression performance of the model [57]. Research on lung cancer by Wang [58], Afshar [59], Astaraki [60], and Liang [61]; on breast cancer by Jiang [62]; on Gastric cancer by Sun [63] and Dong [15]; and on glioma by Chen [64] has indicated that deep learning features are complementary to manual features, and that combining HCR and DLR provides more comprehensive features and enables the model to achieve better results. However, because deep learning features are automatically learned in a black box-like process, they are generally nameless [65].…”
Section: Discussionmentioning
confidence: 99%
“…The model first uses forward propagation in the convolutional layer to connect each layer with other layers in the network and then uses the feature maps of all previous layers as the input of each subsequent layer to construct DenseNet [79,80]. On popular image classification benchmarks, DenseNet can achieve comparable accuracy to ResNet in the ImageNet image classification competition, but it requires significantly fewer parameters [81,82]. In addition, it improves the gradient vanishing problem, and at the same time, it strengthens the feature propagation process and promotes feature reuse through the reorganization of feature maps, reducing the amount of irrelevant computation.…”
Section: Densenetmentioning
confidence: 99%